A review on Insect - fungus interactions with special emphasis on Cordyceps spp. - Kumar, Satish; Sharma, Ved Parkash; Kamal, Shwet (Mushroom Research, 2016)
Insects belong to class Insecta and originally referred to as Hexapoda. Insects are tracheata arthropods where the body is typically divided in to three parts head, thorax and abdomen. The sexes are separate but in some species males may be rare or absent and reproduction may take place parthenogenetically. Insects are the most diverse group of organisms as the number of species of insects is more than any other group of living organisms. Biological attributes such as small size, strong exoskeleton, high mobility through flight, efficient water conservation, rapid reproduction and adoptability are associated with their predominance. In the world some 900 thousand different kind of living insects are known (www.si.edu/encyclopedia). So far much attention has been given to the entomofauna that exist in the canopies of tropical forests of the world. Insects also probably have the largest biomass of the terrestrial animals. It is estimated that there are some 10 quintillion (1018) individual insect alive. Certain social insects have large number of individuals in their nests. An ant nest in Jamaica was calculated to include 6, 30,000 individuals. The second largest group is of fungus flora, which is estimated to be 1.5 million species (Hawksworth, 1992). Therefore, the number of species of fungi would be second only to number of insects. Soil harbour numerous and diverse group of fungi e.g. more that 125 species of soil fungi (mostly Hypomycetes) were reported in depauperate alpine soil in the Rockies of Alberta by Bissett and Parkinson (1980). Insects and fungi are unrelated to each other still there is a lot of interdependence and interactions between them. Interactions may be mutualistic, symbiotic, commensalisms or parasitic. Fungi are highly versatile, plastic and adaptable pleomorphic group often abstract and transport nutrients from diverse substrates which can be used by the insects. Insect-fungus mutulism and commensalisms have co-evolved since they occur in diverse orders and families of Arthropoda and fungi (Batra, 1978). Some macro-fungi especially the polypores and mushrooms are major source of food for numerous insects particularly certain group of beetles (Histeridae, Languriidae) and flies (Sciaridae, Phoradae). On the other hand toxins produced by fungi such as aflatoxin from Aspergillus flavus, beauvericin from Beauveria bassiana and destruxin A and b from Metarrhizium anisopliae are responsible for death of host insect. First record of insect disease is that of Metarrhizium anisopliae in USSR in 1879. The common fungal diseases are caused by the green and white muscardine fungi which have wide host range (Atwal, 1976). On the other hand, there are number of similarities between fungi and arthropods. Both have fuselage like body form with chitin as the main structural component. They are small numerous and specialized in both sexual and asexual activity. They are found in almost all ecological niches. Different types of relationships viz symbiosis, mutualism and parasitism exists between insects and fungi. Existence of some interesting relationship between insects and fungi is reviewed and discussed in this communication.Â